Surveillance Colonoscopies of Synchronous Colorectal Cancer: What Should We Do? - Guo, Chunmei; Wu, Jing; Wang, Yadan; Su, Hui; Wang, Canghai; Liu, Hong (Turkish Journal of Gastroenterology, 2022)
Background: The aim of this study is to investigate the occurrence of metachronous neoplasms at 2-year surveillance colonoscopy for synchronous colorectal cancer patients and the relative risk factors. Methods: Synchronous colorectal cancer patients who underwent surgery or endoscopic resection for colorectal cancer between January 2008 and December 2019 were enrolled. All patients underwent surveillance colonoscopies at least twice within 2 years after operation. Univariate and multivariate analyses were conducted to assess the risk factors for the metachronous neoplasms. Results: Totally 38 patients (male/female: 26/12) were included, with an average age of 64.6 years (±11.5 years) and a mean surveillance interval of 23.47 ± 4.39 months. In 21 of 38 patients (55.3%), metachronous adenoma was detected, including 6 metachronous advanced adenomas. Two patients were detected with metachronous carcinomas. In univariate analysis, male sex, elderly age at diagnosis, and the presence of synchronous adenomas/synchronous advanced adenoma at baseline colonoscopy were associated with the development of metachronous adenoma (P = .037, .047, .013, .039), but not associated with metachronous advanced adenoma (P = 0.455, .746, .503, .269). Patients tends to occur less metachronous advanced adenoma if index colorectal tumors were treated by endoscopic resection (P = .010), but the tendency was not discovered in metachronous adenoma (P = .289). Tumor location (with/ without rectum cancer) was not associated with the development of metachronous lesions (P = .526, .382). On multivariate analysis, the presence of synchronous adenomas at baseline colonoscopy was an independent risk factor for MA during follow-up (odds ratio = 15.0; 95% CI: 1.55-145.22). Conclusion: For postoperative synchronous colorectal cancer patients, doctors should design individual surveillance strategies according to sex, baseline colonoscopy, and operative (or endoscopic) approach of resection. Cite this article as: Guo C, Wu J, Wang Y, Su H, Wang C, Liu H. Surveillance colonoscopies of synchronous colorectal cancer: What should we do? Turk J Gastroenterol. 2023;34(3):234-241.